Why Does the Importance of Education for Health Differ across the United States?. (January 2020) - Kemp, Blakelee R.; Montez, Jennifer Karas
The positive association between educational attainment and adult health ("the gradient") is stronger in some areas of the United States than in others. Explanations for the geographic pattern have not been rigorously investigated. Grounded in a contextual and life-course perspective, the aim of this study is to assess childhood circumstances (e.g., childhood health, compulsory schooling laws) and adult circumstances (e.g., wealth, lifestyles, economic policies) as potential explanations. Using data on U.S.-born adults aged 50 to 59 years at baseline ( n = 13, 095) and followed for up to 16 years across the 1998 to 2014 waves of the Health and Retirement Study, the authors examined how and why educational gradients in morbidity, functioning, and mortality vary across nine U.S. regions. The findings indicate that the gradient is stronger in some areas than others partly because of geographic differences in childhood socioeconomic conditions and health, but mostly because of geographic differences in adult circumstances such as wealth, lifestyles, and economic and tobacco policies.